PENGARUH KUALITAS PELAYANAN, BIAYA, LOKASI DAN PROMOSI TERHADAP KEPUTUSAN MAHASISWA DALAM MEMILIH FAKULTAS EKONOMI UNIVERSITAS MUSI RAWAS - Syafitri, Anggia (Universitas Muhammadiyah Palembang, 2017)
Purpose - The aim of this research is to analyze the impact uses of and service quality, costs, location, promotion of the student decision in selecting the Faculty of Economic, University of Musi Rawas. Â Design/methodology - This research uses a questionnaire and data is collected by having questionnaires of 73 respondents. The population of this research is 272 students of Faculty of Economic, University of Musi Rawas. It is decided that the sample of this research is 73 students. This research uses simple random sampling with certain criteria as the sampling method. Then, the data is analyzed with Multiple Linear regression using computer statistical package. Findings â€“ The author finds that the value variable of the service quality with regression coefficient 0,325, costs with the value regression coefficient -0,452, the value of the location variable regression coefficient 0,649 and promotion of variable regression coefficient 0,509 in partial significant effectÂ on students decision in selecting the Faculty Economic University of Musi Rawas. And the variables of the service quality, cost, location and promotion of the value of Î± (0,000) < 0,05 and the number R square of 0,390 simultaneous significant effect on student decision in selecting the Faculty Economic University of Musi Rawas (Y).